Planning and territorial management in power transmission lines - critical analysis of impacts - Cordeiro, Tiago de Oliveira; Reginato , Vivian da Silva Celestino (Seven Editora, 2023)
The study for the implementation of large engineering works demands constant planning, management, and decision-making to deal with the multitude of problems that may arise during the implementation of a given enterprise. Due to the constant growth and development of cities, the execution of new infrastructure works has been necessary and recurrent in the region, causing some questions and uncertainties on the part of the owners of areas intercepted by power transmission lines, in short, due to the depreciation of the market value of the property. In this sense, this research critically analyzes the impact caused by the right of way of power transmission lines on servant properties in the North of the State of Santa Catarina and highlights the importance of using the multipurpose technical register and integrated and shared spatial information as subsidies to carry out the planning works and carrying out effective management of the territory. DOI: https://doi.org/10.56238/devopinterscie-074